2022
DOI: 10.1590/fst.79721
|View full text |Cite
|
Sign up to set email alerts
|

Ice creams made from cow’s and goat’s milks with different fat concentrations: physical-chemical and sensory properties

Abstract: Goat's milk ice cream made with different fat concentrations was compared with cow's milk ice cream. DSC curves indicated typical behavior of the high water content system. The thermal properties, the enthalpy of fusion (ΔH m ) and the amount of water (w uf ) did not vary with the formulations. For goat's milk ice cream, the viscosity was higher for smaller fat content. Independent of the milk, high fat content promoted greater air incorporation and melting point, indicating a softer and more stable product. G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 41 publications
2
7
0
Order By: Relevance
“…Figure 1A showed that the slope of the shear rate versus shear stress graphs of the ice cream mixes decreased with increasing shear rate, demonstrating that the viscosity of all samples reduced with increasing shear rate (Figure 1B). As seen in Figure 1B, all ice cream mixes showed a clearly pseudoplastic (shear-thinning) behaviour (Carvalho et al, 2022). The highest viscosity value was the ice cream sample prepared with S1 salep (IC-S1).…”
Section: Steady Shear Rheological Properties Of Ice Cream Mixesmentioning
confidence: 89%
“…Figure 1A showed that the slope of the shear rate versus shear stress graphs of the ice cream mixes decreased with increasing shear rate, demonstrating that the viscosity of all samples reduced with increasing shear rate (Figure 1B). As seen in Figure 1B, all ice cream mixes showed a clearly pseudoplastic (shear-thinning) behaviour (Carvalho et al, 2022). The highest viscosity value was the ice cream sample prepared with S1 salep (IC-S1).…”
Section: Steady Shear Rheological Properties Of Ice Cream Mixesmentioning
confidence: 89%
“…Probably the higher concentration of fat was a decisive factor in explaining the lower meltdown rates (Guinard et al, 1997;Stampanoni Koeferli et al 1996;Carvalho et al, 2022;Frøst et al, 2005) observed in the traditional formulation and in formulation 1 (Table 2; Figure 1). On account of fat acts as a physical barrier to the growth of ice crystals (Donhowe et al, 1991) as well as decreases heat transfer (Goff & Hartel, 2013).…”
Section: Physicochemical Characteristics Of Ice Cream Formulationsmentioning
confidence: 99%
“…The fat content, the fat globules, and agglomerates size, as well as their crystallization, the air incorporation, the stabilizers, the ice crystals size and the total solids content, among others, can influence the meltdown rate (Goff and Hartel, 2013). It is also worth noting that the higher fat content tends to promote greater incorporation of air and, consequently, a higher melting point, contributing to a more stable product (Carvalho et al 2022). Thus, the lower the air incorporation rate, the higher is the meltdown rate.…”
Section: Physicochemical Characteristics Of Ice Cream Formulationsmentioning
confidence: 99%
“…The production of ovine’s and caprine’s yoghurts and frozen yoghurts has also followed this trend. Several research works refer to the use of ewe’s [ 32 , 33 , 34 , 35 , 36 , 37 ] and goat’s [ 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ] milks in the production of ice creams with functional properties. In addition, several authors reported the potential medicinal properties of small ruminant’s milks and dairy products [ 51 , 52 , 53 ].…”
Section: Introductionmentioning
confidence: 99%